THE IMPACT OF BUSINESS CAPITAL AND E-COMMERCE ON BANDUNG'S MSME - Sutrisno Sutrisno (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
The quantitative method is used at this stage of the research, which includes reviewing the amount of capital used, the source of capital used, and the technology used by these MSME actors. The goal of this research is to determine how much capital and e-commerce (Papatong.id) influence the turnover or income of MSME players in Bandung, West Java. This study's sample included 47 MSME actors, the majority of whom were micro business actors. This study used multiple linear regression with moderating variables. The findings indicate that capital has a significant or positive influence in the Bandung City, West Java area. Of course, this e-commerce technology (Papatong.id) has a partially positive and significant impact on the turnover or income of MSMEs in Bandung, West Java. Simultaneously, capital and e-commerce technology (Papatong.id) have a very positive and significant influence on the income of MSMEs in the Bandung City area of West Java.